Exploring the Effectiveness of Rehabilitation Programmes on Recidivsm Reduction in Selected Correctional Facilities in Ogun State - Folorunsho, Ogunmefun Muyideen; Esther, Adefuye J.; Adekunle, Olawunmi, T. (Randwick International of Social Science Journal, 2024)
Evidential report gathered from national and international reports indicates the needs for reduction in prisons congestion through the adoption and implementation of quality rehabilitation programme. Prison congestion poses as threat toward rehabilitation programme among the inmates leading to increase in the rate at which recidivism gain it momentum in the correctional facilities in Ogun State, Nigeria. Several national and international publications of the past and present concerning prison congestion, rehabilitation programmes and recidivisms were reviewed to shed comprehensive insights to their various submission with the adoption of rehabilitation theory for the study. Mixed methods were adopted for collection of 330 for the quantitative data through the use of structured questionnaire while 15 in-depth interviews were conducted among the return’s inmates in the four correctional facilities in Ogun state, Nigeria (Ijebu-Ode, Ilaro, Obah, Ibara) respectively. Non-experimental design is adopted with face to serve the instruments to inmates with the aid of probability (Simple random) and non-probability (purposive) sampling techniques. All ethical conditions were collected before conducting the research while descriptive and content methods of data analyses were adopted. The study finds out that improper integration, adoption and implementation of rehabilitation programme will lead to ever-increasing nature of recidivism experienced in Ogun State, Nigeria, therefore it was recommended enhancement of adult literacy, improve number of trained counselor and develop a post-release support program